Characterization of the mechanical properties of chives (allium schoenoprasum l.) (2013)
Chives are aromatic herbs of the onion family and are exported by Colombia. It is a perennial plant that can grow from 20 to 50 cm high. It’s leaves are cylindrical and hollow, similar to those of green onions, but with a smaller diameter (2 to 3 mm). Its harvest is done manually, and sometimes the plant is damaged in this process while the collector is gripping bundles to make the cut. The rheological tests performed were: unidirectional compression, cutting, bending and traction of bunches of leaves, which are how this herb is handled, in order to characterize their mechanical response to the type of forces exerted on them during harvest and postharvest handling. It was found that the compression forces that begin to cause unrecoverable damage or deformations are really small, approximately 1 N. The cutting force needed to rip the bundle at harvest is 35 N on average. The mechanical behavior of the leaves of chives corresponds to a viscoelastic, anisotropic and highly variable material.